Membrane electrode, preparation method thereof and water electrolysis hydrogen production equipment

By using the ultrasonic spraying process on the proton exchange membrane of the membrane electrode and controlling the spraying direction and distance, the problem of excessive thickness at the edge of the catalytic layer of the membrane electrode caused by the traditional spraying process is solved, and the performance stability of the membrane electrode is improved.

CN119320957APending Publication Date: 2025-01-17JIANGSU TRINA GREEN HYDROGEN TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411539665.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The film electrode catalytic layer prepared by the traditional spraying process has a problem of large thickness at the edges, which affects the performance stability of the film electrode.

Method used

Use an ultrasonic spraying process to coat the catalyst slurry on the proton exchange membrane, and control the distance between the starting end of the spraying and the first end of the proton exchange membrane and the distance between the end of the spraying and the second end of the proton exchange membrane to be greater than or equal to 5mm, so that Avoid thick edges of the catalytic layer.

Benefits of technology

It effectively avoids the problem of thick catalytic layer at the edge of the membrane electrode caused by the traditional spraying process, and improves the performance stability of the membrane electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320957A_ABST
    Figure CN119320957A_ABST
Patent Text Reader

Abstract

The invention relates to a membrane electrode, a preparation method thereof and water electrolysis hydrogen production equipment. The preparation method of the membrane electrode comprises the following steps: providing the proton exchange membrane; coating catalyst slurry on the proton exchange membrane by adopting an ultrasonic spraying process, and drying to obtain the membrane electrode, the spraying direction of the ultrasonic spraying process is a direction from a first end of the proton exchange membrane to an opposite second end, a spraying starting line end is located at a position far away from the first end by a first distance from the second end, and a spraying stopping end is located at a position far away from the first end by a second distance from the second end; the first distance and the second distance are both larger than or equal to 5 mm. According to the preparation method of the membrane electrode, the problem that a catalyst layer on the edge of the membrane electrode is too thick due to traditional spraying can be avoided, and the performance stability of the membrane electrode is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrolytic hydrogen production, and in particular to a membrane electrode and a preparation method thereof, and water electrolysis hydrogen production equipment. Background Art

[0002] The current hydrogen production technologies mainly include: alkaline water electrolysis (AWE), proton exchange membrane water electrolysis (PEM), anion exchange membrane water electrolysis (AEM) and solid oxide electrolysis (SOEC).

[0003] The core component of hydrogen production by water electrolysis is the membrane electrode, which directly determines the performance and stability of hydrogen production by water electrolysis, and further determines the efficiency and stability of the hydrogen production device by water electrolysis. The membrane electrode for hydrogen production by water electrolysis is an important component of the PEM water electrolysis hydrogen production device, which includes a proton exchange membrane and an anode catalyst layer and a cathode catalyst layer arranged on both sides of the proton exchange membrane. At present, the main preparation processes of membrane electrodes include thermal transfer, spraying, and scraping. However, after research, the inventors found that the catalyst layer prepared by the traditional spraying process has a problem of being thicker at the edge of the membrane electrode than other areas, which will affect the performance stability of the membrane electrode. Summary of the invention

[0004] Based on this, it is necessary to provide a membrane electrode and a preparation method thereof, and a water electrolysis hydrogen production device to solve the problem that the catalyst layer prepared by the traditional spraying process is too thick at the edge of the membrane electrode.

[0005] One of the purposes of the present invention is to provide a method for preparing a membrane electrode, the scheme is as follows:

[0006] A method for preparing a membrane electrode comprises the following steps:

[0007] Providing proton exchange membranes;

[0008] The catalyst slurry is coated on the proton exchange membrane by ultrasonic spraying process, and then dried to obtain the membrane electrode;

[0009] The spraying direction of the ultrasonic spraying process is from the first end of the proton exchange membrane to the opposite second end, and the spraying starting line end is located at a first distance away from the first end to the second end, and the spraying ending end is located at a second distance away from the second end to the first end, and the first distance and the second distance are both greater than or equal to 5 mm.

[0010] In one embodiment, the first distance and / or the second distance is 5 mm to 30 mm.

[0011] In one embodiment, the proton exchange membrane is rectangular, and the first end and the second end are two parallel ends of the proton exchange membrane.

[0012] In one embodiment, the parameters of the ultrasonic spraying process include: a spraying flow rate of 0.4 ml / min to 10 ml / min, a spraying speed of 10 mm / s to 200 mm / s, and a spraying interval of 5 mm to 20 mm.

[0013] In one embodiment, the step of coating the catalyst slurry on the proton exchange membrane using an ultrasonic spraying process comprises:

[0014] The anode catalyst slurry and the cathode catalyst slurry are respectively coated on both sides of the proton exchange membrane by using an ultrasonic spraying process.

[0015] In one embodiment, the anode catalyst slurry comprises an anode catalyst, a first binder, and a first solvent in a mass ratio of (5-10): (10-20): (55-100).

[0016] The cathode catalyst slurry comprises a cathode catalyst, a second binder and a second solvent in a mass ratio of (5-10): (10-20): (55-100).

[0017] In one embodiment, the first binder and the second binder are independently selected from one or more of perfluorosulfonic acid resin, polysulfone, and polyphenylene sulfide.

[0018] In one embodiment, the first solvent and the second solvent independently include an alcohol solvent and water in a mass ratio of (25-40): (30-60).

[0019] In one embodiment, the particle size of the anode catalyst is less than or equal to 40 μm.

[0020] In one of the embodiments, the cathode catalyst has a particle size less than or equal to 40 μm.

[0021] In one embodiment, the binder is perfluorosulfonic acid resin.

[0022] In one embodiment, the solvent comprises n-propanol and water in a mass ratio of (25-40): (30-60).

[0023] In one embodiment, the anode catalyst is selected from one or more of a Pt / C catalyst, a PtRu / C catalyst, a PtIr / C catalyst, a PtCo / C catalyst, a PtCoMn / C catalyst, a PtNi / C catalyst, a Ru / C catalyst, and an IrRu / C catalyst.

[0024] In one embodiment, the cathode catalyst is a Pt / C catalyst.

[0025] In one embodiment, the drying temperature is 50°C to 90°C.

[0026] Another object of the present invention is to provide a membrane electrode, the scheme is as follows:

[0027] A membrane electrode, characterized in that it is prepared by the preparation method described in any of the above embodiments.

[0028] Another object of the present invention is to provide a water electrolysis hydrogen production device, the scheme is as follows:

[0029] A water electrolysis hydrogen production device comprises the membrane electrode.

[0030] Compared with the traditional solution, the membrane electrode and its preparation method, and the water electrolysis hydrogen production equipment have the following beneficial effects:

[0031] The above-mentioned membrane electrode preparation method adopts ultrasonic spraying technology to coat the catalyst slurry on the proton exchange membrane, and controls the distance between the spraying starting end and the first end of the proton exchange membrane to be more than 5 mm, and the distance between the spraying ending end and the second end of the proton exchange membrane to be more than 5 mm. This can avoid the problem of thick catalyst layer at the edge of the membrane electrode caused by traditional spraying and improve the performance stability of the membrane electrode.

[0032] The above-mentioned water electrolysis hydrogen production equipment has the above-mentioned membrane electrode and can achieve corresponding technical effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] FIG1 is a schematic diagram of the structure of a membrane electrode according to an embodiment;

[0034] FIG2 is a schematic diagram of spraying catalyst slurry on a proton exchange membrane;

[0035] Figure 3 shows the constant current density of 10000A / m 2 The following is a comparison chart of the stability of the membrane electrode prepared in the embodiment and the comparative example. DETAILED DESCRIPTION

[0036] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are shown in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. The purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0037] It should be noted that when an element is referred to as being "disposed on" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only and do not represent the only implementation method.

[0038] In the description of the present invention, it should be understood that the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number or order of the indicated technical features.

[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0040] The method for preparing a membrane electrode of one embodiment comprises the following steps:

[0041] Step S1, providing a proton exchange membrane;

[0042] Step S2 , as shown in FIG. 1 , uses an ultrasonic spraying process to coat the catalyst slurry on the proton exchange membrane 11 , and performs a drying process to obtain a membrane electrode 10 .

[0043] More specifically, the anode catalyst slurry and the cathode catalyst slurry are respectively coated on both sides of the proton exchange membrane 11 by ultrasonic spraying process, and dried to form the anode catalyst layer 12 and the cathode catalyst layer 13 respectively, thereby obtaining the membrane electrode 10.

[0044] As shown in Fig. 2, the spraying direction of the ultrasonic spraying process is from the first end 111 of the proton exchange membrane to the opposite second end 112. The spraying starting line end 21 is located at a first distance from the first end 111 to the second end 112, and the spraying ending end 22 is located at a second distance from the second end 112 to the first end 111. The first distance and the second distance are both greater than or equal to 5 mm.

[0045] The above-mentioned membrane electrode preparation method adopts ultrasonic spraying technology to coat the catalyst slurry on the proton exchange membrane, and controls the distance between the spraying starting end and the first end of the proton exchange membrane to be more than 5 mm, and the distance between the spraying ending end and the second end of the proton exchange membrane to be more than 5 mm. This can avoid the problem of thick catalyst layer at the edge of the membrane electrode caused by traditional spraying and improve the performance stability of the membrane electrode.

[0046] In some of the examples, the spraying start end of the ultrasonic spraying process is at a position where the first end of the proton exchange membrane is 5mm~30mm extended, that is, the first distance is 5mm~30mm. Further, in some of the examples, the spraying start end is at a position where the first end of the proton exchange membrane is 5mm~20mm extended. Further, in some of the examples, the spraying start end is at a position where the first end of the proton exchange membrane is 5mm~10mm extended. In some specific examples, the distance between the spraying start end and the first end of the proton exchange membrane is 5mm, 10mm, 15mm, 20mm, 25mm, 30mm, etc.

[0047] In some of these examples, the spraying termination end of the ultrasonic spraying process is at a position where the second end of the proton exchange membrane is extended by 5mm~30mm, that is, the second distance is 5mm~30mm. Further, in some of these examples, the spraying termination end is at a position where the second end of the proton exchange membrane is extended by 5mm~20mm. Further, in some of these examples, the spraying termination end is at a position where the second end of the proton exchange membrane is extended by 5mm~10mm. In some specific examples, the distance between the spraying termination end and the second end of the proton exchange membrane is 5mm, 10mm, 15mm, 20mm, 25mm, 30mm, etc.

[0048] In some of the examples, when spraying the catalyst slurry, the spraying is started with a delay of 0.01 to 1 second from the epitaxial position of the starting point. In some of the examples, when spraying the catalyst slurry, the spraying is started with a delay of 0.02 to 0.05 second from the epitaxial position of the starting point.

[0049] The traditional membrane electrode prepares a gas diffusion layer on the proton exchange membrane, and then prepares a catalyst layer on the gas diffusion layer. However, the inventors have found through research that preparing a catalyst layer on a gas diffusion layer will cause some catalyst particles to enter the pores of the gas diffusion layer, which will not only affect gas transmission, but also reduce the utilization rate of the catalyst. In addition, when preparing membrane electrodes by the transfer method, the catalyst layer will be damaged due to uneven force on the edge of the transfer medium, and the catalyst layer cannot be completely transferred to the membrane layer. For this reason, it is preferred to spray the catalyst slurry directly on the surface of the proton exchange membrane, thereby effectively reducing the phenomenon of uneven force on the edge of the medium, and also improving the utilization efficiency of the catalyst in the membrane electrode and reducing the waste of the catalyst.

[0050] To improve the uniformity of ultrasonic spraying of the catalyst slurry, in some examples, the ultrasonic spraying process uses a straight spray path for spraying.

[0051] To improve the uniformity of ultrasonic spraying of the catalyst slurry, in some of the examples, the spraying flow rate of the ultrasonic spraying process is 0.4ml / min~10ml / min. Further, in some of the examples, the spraying flow rate of the ultrasonic spraying process is 2ml / min~8ml / min. In some specific examples, the spraying flow rate is, for example, 0.4ml / min, 1ml / min, 2ml / min, 3ml / min, 4ml / min, 5ml / min, 6ml / min, 7ml / min, 8ml / min, 9ml / min, 10ml / min, etc.

[0052] To improve the uniformity of ultrasonic spraying of the catalyst slurry, in some of the examples, the ultrasonic spraying process is sprayed at a uniform spraying speed.

[0053] To improve the uniformity of ultrasonic spraying of the catalyst slurry, in some of the examples, the spraying speed of the ultrasonic spraying process is 10 mm / s to 200 mm / s. Further, in some of the examples, the spraying speed of the ultrasonic spraying process is 50 mm / s to 150 mm / s. In some specific examples, the spraying speed is 10 mm / s, 20 mm / s, 40 mm / s, 60 mm / s, 80 mm / s, 100 mm / s, 120 mm / s, 140 mm / s, 160 mm / s, 180 mm / s, 200 mm / s, etc.

[0054] To improve the uniformity of ultrasonic spraying of the catalyst slurry, in some of the examples, the spraying interval of the ultrasonic spraying process (i.e., the distance between the nozzle and the proton exchange membrane) is 5 mm to 20 mm. Further, in some of the examples, the spraying interval of the ultrasonic spraying process is 10 mm to 15 mm. In some specific examples, the spraying interval is 5 mm, 6 mm, 8 mm, 10 mm, 12 mm, 14 mm, 16 mm, 18 mm, 20 mm, etc.

[0055] It can be understood that the number of ultrasonic spraying is not limited to only once, and multiple spraying can be performed in the above-mentioned spraying direction, for example, drying after each spraying, and then spraying again until the thickness of the catalyst layer reaches the requirement.

[0056] In some of these examples, the proton exchange membrane is a Nafion membrane (perfluorosulfonic acid membrane).

[0057] In some of the examples, the thickness of the proton exchange membrane is 50 μm to 200 μm. Further, in some of the examples, the thickness of the proton exchange membrane is 120 μm to 190 μm.

[0058] During the ultrasonic spraying process, the proton exchange membrane is placed on the vacuum adsorption platform 30, and the proton exchange membrane is evenly spread out by vacuum adsorption, which is beneficial to the uniform spraying of the catalyst slurry on the proton exchange membrane.

[0059] To improve the uniformity of ultrasonic spraying of the anode catalyst slurry, in some examples, the anode catalyst slurry comprises an anode catalyst, a first binder, and a first solvent in a mass ratio of (5-10):(10-20):(55-100).

[0060] In order to improve the uniformity of ultrasonic spraying of the anode catalyst slurry, in some examples, the first binder is one or more of perfluorosulfonic acid resin, polysulfone and polyphenylene sulfide. Further, the first binder is preferably perfluorosulfonic acid resin.

[0061] In order to improve the uniformity of ultrasonic spraying of the anode catalyst slurry, in some examples, the first solvent includes an alcohol solvent and water in a mass ratio of (25-40): (30-60). Among them, the alcohol solvent is, for example, but not limited to, methanol, ethanol, n-propanol, and isopropanol. Furthermore, the alcohol solvent is preferably n-propanol.

[0062] In order to improve the uniformity of ultrasonic spraying of the anode catalyst slurry, in some examples, the particle size of the anode catalyst is less than or equal to 40 μm. For example, the particle size of the anode catalyst is 5 μm to 40 μm, specifically 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, etc.

[0063] In some of the examples, the anode catalyst used in the anode catalyst slurry includes active metal elements Pt, Ru, Pd, Ir and their alloys, and one or more of Ni, Co, Mo, Cr, alloys, phosphides and nitrides; the carrier can be carbon, oxides, etc. The anode catalyst is preferably one or more of Pt / C catalyst, PtRu / C catalyst, PtIr / C catalyst, PtCo / C catalyst, PtCoMn / C catalyst, PtNi / C catalyst, Ru / C catalyst, IrRu / C catalyst.

[0064] To improve the uniformity of ultrasonic spraying of the cathode catalyst slurry, in some examples, the cathode catalyst slurry comprises a cathode catalyst, a first binder, and a first solvent in a mass ratio of (5-10):(10-20):(55-100).

[0065] In order to improve the uniformity of ultrasonic spraying of the cathode catalyst slurry, in some examples, the first binder is one or more of perfluorosulfonic acid resin, polysulfone and polyphenylene sulfide. Further, the first binder is preferably perfluorosulfonic acid resin.

[0066] In order to improve the uniformity of ultrasonic spraying of the cathode catalyst slurry, in some examples, the first solvent includes an alcohol solvent and water in a mass ratio of (25-40): (30-60). Among them, the alcohol solvent is, for example, but not limited to, methanol, ethanol, n-propanol, isopropanol, etc. Further, the alcohol solvent is preferably n-propanol.

[0067] In order to improve the uniformity of ultrasonic spraying of cathode catalyst slurry, in some examples, the particle size of cathode catalyst is less than or equal to 40 μm. For example, the particle size of cathode catalyst is 5 μm to 40 μm, specifically 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, etc.

[0068] In some of the examples, the cathode catalyst used in the cathode catalyst slurry includes active metal elements Pt, Ru, Pd, Ir, and alloys thereof, and one or more of Ni, Co, Mo, Cr, alloys, phosphides, and nitrides; the carrier may be carbon, oxides, etc. The cathode catalyst preferably uses a Pt / C catalyst.

[0069] The above example combines the optimization of the catalyst slurry formula with the ultrasonic spraying process, so that the catalyst slurry increases the firmness of the catalyst particles during the spraying and drying process, reducing the risk of catalyst falling off; at the same time, the spraying makes the catalyst more evenly distributed on the proton exchange membrane.

[0070] In some examples, the drying temperature is 50°C to 90°C, specifically 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, etc., or a range between any two of the above values. This temperature range is conducive to drying to form a uniform catalyst film layer, reducing the swelling of the membrane electrode and reducing the occurrence of drying cracks in the membrane electrode.

[0071] Furthermore, in some of the examples, the drying temperature is 60° C. to 80° C. This temperature range is close to the azeotropic point of n-propanol and water, which is conducive to the volatilization of the solvent, reduces the swelling of the membrane electrode, and reduces the occurrence of drying cracks in the membrane electrode.

[0072] In summary, the present invention prepares a membrane electrode with high thickness uniformity by optimizing the catalyst slurry formula and ultrasonic spraying process. Even if the catalyst types and ratios are different, optimizing the spraying flow rate, spraying speed, spraying interval, spraying time and other parameters can effectively avoid the catalyst slurry from gathering at the edge of the membrane, improve the uniformity of the catalyst slurry on the membrane electrode, and help increase the stability of the performance of the membrane electrode when in use.

[0073] Furthermore, the present invention also provides a membrane electrode, which is prepared by any of the preparation methods in the above examples.

[0074] Furthermore, the present invention also provides a water electrolysis hydrogen production device, which has the above-mentioned membrane electrode.

[0075] The following specific examples are provided to further illustrate the present invention. The present invention provides the following specific examples for a better understanding of the present invention, but is not limited to the specific implementation methods and does not limit the protection scope of the present invention.

[0076] Example 1

[0077] The present embodiment provides a membrane electrode and a method for preparing the same. The method for preparing the membrane electrode of the present embodiment comprises the following steps:

[0078] Preparation of catalyst slurry:

[0079] n-Propanol and water are mixed in a weight ratio of 2:1 to obtain a mixed solution. Perfluorosulfonic acid resin is added to the mixed solution and stirred and dispersed to obtain a binder solution. The content of the perfluorosulfonic acid resin in the binder solution is 10wt%.

[0080] Preparation of catalyst slurry:

[0081] The anode catalyst and cathode catalyst are mixed with water respectively, and n-propanol and the above-mentioned binder solution are added thereto in turn, stirred and mixed, and then ground, filtered and vacuum defoamed in turn to obtain anode catalyst slurry and cathode catalyst slurry. In the catalyst slurry, the mass ratio of catalyst, binder, n-propanol and water is 6:17:35:42. Among them, the cathode catalyst is a platinum carbon catalyst, and the platinum content is 50wt%. The anode catalyst is an iridium oxide catalyst, and the iridium content is extremely low.

[0082] Preparation of membrane electrode:

[0083] The anode catalyst slurry and cathode catalyst slurry were added to the material tank A and material tank B of the spraying equipment respectively. A proton exchange membrane (Nafion membrane) with a thickness of 125 μm was laid flat on the vacuum adsorption platform for adsorption and fixation, and the temperature of the heating plate was set to 80°C.

[0084] The required spraying size is 180mm×100mm, and the spraying direction is delayed, extending 8mm in length and 5mm in width, so the spraying coverage area is 196mm×110mm. The delayed spraying time is 0.02s to start spraying the catalyst slurry, and the spraying is stopped in advance at 5mm at the spraying end point. The spraying flow rate is set to 0.6ml / min, the spraying speed is set to 100mm / s, and the spraying interval is set to 5mm to spray the catalyst slurry. After the anode catalyst slurry spraying is completed, the spraying surface is automatically switched, and the spraying equipment switches the nozzle to spray the cathode catalyst slurry. The operation is the same as the anode catalyst spraying.

[0085] After spraying, the thickness of the sprayed membrane electrode and the performance of the membrane electrode were tested, and the test results are shown in Table 1 and Table 2. At the same time, the stability of the membrane electrode was tested as shown in Figure 3.

[0086] Example 2

[0087] The present embodiment provides a membrane electrode and a method for preparing the same. The method for preparing the membrane electrode of the present embodiment comprises the following steps:

[0088] Preparation of catalyst slurry:

[0089] n-Propanol and water are mixed in a weight ratio of 3:1 to obtain a mixed solution. Perfluorosulfonic acid resin is added to the mixed solution and stirred and dispersed to obtain a binder solution. The content of the perfluorosulfonic acid resin in the binder solution is 8wt%.

[0090] Preparation of catalyst slurry:

[0091] The anode catalyst and cathode catalyst are mixed with water respectively, and n-propanol and the above-mentioned binder solution are added thereto in turn, stirred and mixed, and then ground, filtered and vacuum defoamed in turn to obtain anode catalyst slurry and cathode catalyst slurry. In the catalyst slurry, the mass ratio of catalyst, binder, n-propanol and water is 5:15:33:47. Among them, the cathode catalyst is a platinum carbon catalyst, and the platinum content is 55wt%. The anode catalyst is an iridium oxide catalyst with an extremely low iridium content.

[0092] Preparation of membrane electrode:

[0093] The anode catalyst slurry and cathode catalyst slurry were added to the material tank A and material tank B of the spraying equipment respectively. A proton exchange membrane (Nafion membrane) with a thickness of 125 μm was laid flat on the vacuum adsorption platform for adsorption and fixation, and the temperature of the heating plate was set to 70°C.

[0094] The required spraying size is 180mm×100mm, and the spraying direction is delayed, extending 8mm in length and 5mm in width, so the spraying coverage area is 196mm×110mm. The delayed spraying time is 0.03s to start spraying the catalyst slurry, and the spraying is stopped in advance at 5mm at the spraying end point. The spraying flow rate is set to 0.7ml / min, the spraying speed is set to 100mm / s, and the spraying interval is set to 5mm to spray the catalyst slurry. After the anode catalyst slurry spraying is completed, the spraying surface is automatically switched, and the spraying equipment switches the nozzle to spray the cathode catalyst slurry. The operation is the same as the anode catalyst spraying.

[0095] After spraying, the thickness of the sprayed membrane electrode and the performance of the membrane electrode were tested, and the test results are shown in Table 1 and Table 2. At the same time, the stability of the membrane electrode was tested as shown in Figure 3.

[0096] Example 3

[0097] The present embodiment provides a membrane electrode and a method for preparing the same. The method for preparing the membrane electrode of the present embodiment comprises the following steps:

[0098] Preparation of catalyst slurry:

[0099] The n-propanol and water are mixed in a weight ratio of 2:1 to obtain a mixed solution. Perfluorosulfonic acid resin is added to the mixed solution and stirred and dispersed to obtain a binder solution. The content of the perfluorosulfonic acid resin in the binder solution is 6wt%.

[0100] Preparation of catalyst slurry:

[0101] The anode catalyst and cathode catalyst are mixed with water respectively, and n-propanol and the above-mentioned binder solution are added thereto in turn, stirred and mixed, and then ground, filtered and vacuum defoamed in turn to obtain anode catalyst slurry and cathode catalyst slurry. In the catalyst slurry, the mass ratio of catalyst, binder, n-propanol and water is 8:16:34:42. Among them, the cathode catalyst is a platinum carbon catalyst, and the platinum content is 50wt%. The anode catalyst is an iridium oxide catalyst, and the iridium content is extremely low.

[0102] Preparation of membrane electrode:

[0103] The anode catalyst slurry and cathode catalyst slurry were added to the material tank A and material tank B of the spraying equipment respectively. A proton exchange membrane (Nafion membrane) with a thickness of 125 μm was laid flat on the vacuum adsorption platform for adsorption and fixation, and the temperature of the heating plate was set to 65°C.

[0104] The required spraying size is 180mm×100mm, and the spraying direction is delayed, extending 9mm in length and 6mm in width, so the spraying coverage area is 198mm×112mm. The delayed spraying time is 0.01s to start spraying the catalyst slurry, and the spraying is stopped in advance when the spraying end point is 6mm. The spraying flow rate is set to 0.6ml / min, the spraying speed is set to 100mm / s, and the spraying interval is set to 5mm to spray the catalyst slurry. After the anode catalyst slurry spraying is completed, the spraying surface is automatically switched, and the spraying equipment switches the nozzle to spray the cathode catalyst slurry. The operation is the same as the anode catalyst spraying.

[0105] After spraying, the thickness of the sprayed membrane electrode and the performance of the membrane electrode were tested, and the test results are shown in Table 1 and Table 2. At the same time, the stability of the membrane electrode was tested as shown in Figure 3.

[0106] Example 4

[0107] The present embodiment provides a membrane electrode and a method for preparing the same. The method for preparing the membrane electrode of the present embodiment comprises the following steps:

[0108] Preparation of catalyst slurry:

[0109] n-Propanol and water are mixed in a weight ratio of 2:1 to obtain a mixed solution. Perfluorosulfonic acid resin is added to the mixed solution and stirred and dispersed to obtain a binder solution. The content of the perfluorosulfonic acid resin in the binder solution is 5wt%.

[0110] Preparation of catalyst slurry:

[0111] The anode catalyst and cathode catalyst are mixed with water respectively, and n-propanol and the above-mentioned binder solution are added thereto in turn, stirred and mixed, and then ground, filtered and vacuum defoamed in turn to obtain anode catalyst slurry and cathode catalyst slurry. In the catalyst slurry, the mass ratio of catalyst, binder, n-propanol and water is 10:20:40:30. Among them, the cathode catalyst is a platinum carbon catalyst, and the platinum content is 40wt%. The anode catalyst is an iridium oxide catalyst, and the iridium content is extremely low.

[0112] Preparation of membrane electrode:

[0113] The anode catalyst slurry and cathode catalyst slurry were added to the material tank A and material tank B of the spraying equipment respectively. A proton exchange membrane (Nafion membrane) with a thickness of 125 μm was laid flat on the vacuum adsorption platform for adsorption and fixation, and the temperature of the heating plate was set to 50°C.

[0114] The required spraying size is 180mm×100mm, and the spraying direction is delayed, extending 10mm in length and 8mm in width, so the spraying coverage area is 200mm×116mm. The delayed spraying time is 0.05s to start spraying the catalyst slurry, and the spraying is stopped in advance at 10mm at the spraying end point. The spraying flow rate is set to 1.0ml / min, the spraying speed is set to 200mm / s, and the spraying interval is set to 20mm to spray the catalyst slurry. After the anode catalyst slurry spraying is completed, the spraying surface is automatically switched, and the spraying equipment switches the nozzle to spray the cathode catalyst slurry. The operation is the same as the anode catalyst spraying.

[0115] After spraying, the thickness of the sprayed membrane electrode and the performance of the membrane electrode were tested, and the test results are shown in Table 1 and Table 2. At the same time, the stability of the membrane electrode was tested as shown in Figure 3.

[0116] Comparative Example 1

[0117] The preparation method of the membrane electrode of this comparative example comprises the following steps:

[0118] Preparation of catalyst slurry:

[0119] n-Propanol and water are mixed in a weight ratio of 2:1 to obtain a mixed solution. Perfluorosulfonic acid resin is added to the mixed solution and stirred and dispersed to obtain a binder solution. The content of the perfluorosulfonic acid resin in the binder solution is 5wt%.

[0120] Preparation of catalyst slurry:

[0121] The anode catalyst and cathode catalyst are mixed with water respectively, and n-propanol and the above-mentioned binder solution are added thereto in turn, stirred and mixed, and then ground, filtered and vacuum defoamed in turn to obtain anode catalyst slurry and cathode catalyst slurry. In the catalyst slurry, the mass ratio of catalyst, binder, n-propanol and water is 10:20:30:40. Among them, the cathode catalyst is a platinum carbon catalyst, and the platinum content is 50wt%. The anode catalyst is an iridium oxide catalyst, and the iridium content is extremely low.

[0122] Preparation of membrane electrode:

[0123] The anode catalyst slurry and cathode catalyst slurry were added to the material tank A and material tank B of the spraying equipment respectively. A proton exchange membrane (Nafion membrane) with a thickness of 125 μm was laid flat on the vacuum adsorption platform for adsorption and fixation, and the temperature of the heating plate was set to 70°C.

[0124] The required spraying size is 180mm×100mm, and the spraying direction is delayed, extending 10mm in length and 7mm in width, so the spraying coverage area is 200mm×114mm. The delayed spraying time is 0.03s to start spraying the catalyst slurry, and the spraying is stopped in advance at 10mm at the spraying end point. The spraying flow rate is set to 0.7ml / min, the spraying speed is set to 90mm / s, and the spraying interval is set to 6mm to spray the catalyst slurry. After the anode catalyst slurry spraying is completed, the spraying surface is automatically switched, and the spraying equipment switches the nozzle to spray the cathode catalyst slurry. The operation is the same as the anode catalyst spraying.

[0125] After spraying, the thickness of the sprayed membrane electrode and the performance of the membrane electrode were tested, and the test results are shown in Table 1 and Table 2. At the same time, the stability of the membrane electrode was tested as shown in Figure 3.

[0126] Comparative Example 2

[0127] The preparation method of the membrane electrode of this comparative example comprises the following steps:

[0128] Preparation of catalyst slurry:

[0129] n-Propanol and water are mixed in a weight ratio of 2:1 to obtain a mixed solution. Perfluorosulfonic acid resin is added to the mixed solution and stirred and dispersed to obtain a binder solution. The content of the perfluorosulfonic acid resin in the binder solution is 10wt%.

[0130] Preparation of catalyst slurry:

[0131] The anode catalyst and cathode catalyst are mixed with water respectively, and n-propanol and the above-mentioned binder solution are added thereto in turn, stirred and mixed, and then ground, filtered and vacuum defoamed in turn to obtain anode catalyst slurry and cathode catalyst slurry. In the catalyst slurry, the mass ratio of catalyst, binder, n-propanol and water is 6:17:35:42. Among them, the cathode catalyst is a platinum carbon catalyst, and the platinum content is 50wt%. The anode catalyst is an iridium oxide catalyst, and the iridium content is extremely low.

[0132] Preparation of membrane electrode:

[0133] The anode catalyst slurry and cathode catalyst slurry were added to the material tank A and material tank B of the spraying equipment respectively. A proton exchange membrane (Nafion membrane) with a thickness of 125 μm was laid flat on the vacuum adsorption platform for adsorption and fixation, and the temperature of the heating plate was set to 80°C.

[0134] The required spraying size is 180mm×100mm, and the spraying direction is delayed, extending 8mm in length and 5mm in width, so the spraying coverage area is 196mm×110mm. The delayed spraying time is 0.02s to start spraying the catalyst slurry, and the spraying is stopped in advance at 5mm at the spraying end point. The spraying flow rate is set to 0.6ml / min, the spraying speed is set to 100mm / s, and the spraying interval is set to 5mm to spray the catalyst slurry. After the anode catalyst slurry spraying is completed, the spraying surface is automatically switched, and the spraying equipment switches the nozzle to spray the cathode catalyst slurry. The operation is the same as the anode catalyst spraying.

[0135] After spraying, the thickness of the sprayed membrane electrode and the performance of the membrane electrode were tested, and the test results are shown in Table 1 and Table 2. At the same time, the stability of the membrane electrode was tested as shown in Figure 3.

[0136] Comparative Example 3

[0137] The preparation method of the membrane electrode of this comparative example comprises the following steps:

[0138] Preparation of catalyst slurry:

[0139] n-Propanol and water are mixed in a weight ratio of 2:1 to obtain a mixed solution. Perfluorosulfonic acid resin is added to the mixed solution and stirred and dispersed to obtain a binder solution. The content of the perfluorosulfonic acid resin in the binder solution is 10wt%.

[0140] Preparation of catalyst slurry:

[0141] The anode catalyst and the cathode catalyst are mixed with water respectively, and n-propanol and the above-mentioned binder solution are added thereto in turn, stirred and mixed, and then ground, filtered and vacuum defoamed in turn to obtain anode catalyst slurry and cathode catalyst slurry. In the catalyst slurry, the mass ratio of catalyst, binder, n-propanol and water is 6:17:35:42. Among them, the cathode catalyst is a platinum carbon catalyst, and the platinum content is 50wt%. The anode catalyst is a platinum-cobalt alloy catalyst, and the platinum content is 50wt%.

[0142] Preparation of membrane electrode:

[0143] The anode catalyst slurry and cathode catalyst slurry were added to the material tank A and material tank B of the spraying equipment respectively. A proton exchange membrane (Nafion membrane) with a thickness of 180 μm was laid flat on the vacuum adsorption platform for adsorption and fixation, and the temperature of the heating plate was set to 80°C.

[0144] The required spraying size is 180mm×100mm, and the spraying direction is delayed, extending 8mm in length and 5mm in width, so the spraying coverage area is 196mm×110mm. The delayed spraying time is 0.02s to start spraying the catalyst slurry, and the spraying is stopped in advance at 5mm at the spraying end point. The spraying flow rate is set to 0.6ml / min, the spraying speed is set to 100mm / s, and the spraying interval is set to 5mm to spray the catalyst slurry. After the anode catalyst slurry spraying is completed, the spraying surface is automatically switched, and the spraying equipment switches the nozzle to spray the cathode catalyst slurry. The operation is the same as the anode catalyst spraying.

[0145] After spraying, the thickness of the sprayed membrane electrode and the performance of the membrane electrode were tested, and the test results are shown in Table 1 and Table 2. At the same time, the stability of the membrane electrode was tested as shown in Figure 3.

[0146] Comparative Example 4

[0147] The preparation method of the membrane electrode of this comparative example comprises the following steps:

[0148] Preparation of catalyst slurry:

[0149] n-Propanol and water are mixed in a weight ratio of 3:1 to obtain a mixed solution. Polysulfone resin is added to the mixed solution and stirred and dispersed to obtain a binder solution. The content of the polysulfone resin in the binder solution is 10wt%.

[0150] Preparation of catalyst slurry:

[0151] The anode catalyst and cathode catalyst are mixed with water respectively, and n-propanol and the above-mentioned binder solution are added thereto in turn, stirred and mixed, and then ground, filtered and vacuum defoamed in turn to obtain anode catalyst slurry and cathode catalyst slurry. In the catalyst slurry, the mass ratio of catalyst, binder, n-propanol and water is 7:15:45:33. Among them, the cathode catalyst is a platinum carbon catalyst, and the platinum content is 50wt%. The anode catalyst is an iridium oxide catalyst, and the iridium content is extremely low.

[0152] Preparation of membrane electrode:

[0153] The anode catalyst slurry and cathode catalyst slurry were added to the material tank A and material tank B of the spraying equipment respectively. A proton exchange membrane (Nafion membrane) with a thickness of 125 μm was laid flat on the vacuum adsorption platform for adsorption and fixation, and the temperature of the heating plate was set to 80°C.

[0154] The required spraying size is 180mm×100mm, and the spraying direction is delayed, extending 8mm in length and 5mm in width, so the spraying coverage area is 196mm×110mm. The delayed spraying time is 0.05s to start spraying the catalyst slurry, and the spraying is stopped in advance at 7mm at the spraying end point. The spraying flow rate is set to 2ml / min, the spraying speed is set to 100mm / s, and the spraying interval is set to 5mm to spray the catalyst slurry. After the anode catalyst slurry spraying is completed, the spraying surface is automatically switched, and the spraying equipment switches the nozzle to spray the cathode catalyst slurry. The operation is the same as the anode catalyst spraying.

[0155] After spraying, the thickness of the sprayed membrane electrode and the performance of the membrane electrode were tested, and the test results are shown in Table 1 and Table 2. At the same time, the stability of the membrane electrode was tested as shown in Figure 3.

[0156] Table 1 Comparison of membrane electrode thickness uniformity

[0157]

[0158] In Table 1, the thickness refers to the total thickness of the proton membrane and the catalyst layer.

[0159] From the results in Table 1, it can be seen that in Examples 1 to 4, by optimizing the catalyst formulation and ultrasonic spraying process, the catalyst slurry is evenly distributed on the proton membrane, and there is no obvious slurry accumulation phenomenon. Compared with Comparative Example 4, it can be seen that changing the type of polymer binder resin increases the viscosity of the catalyst slurry, reduces the uniformity of the ultrasonic spraying liquid, and reduces the uniformity of the thickness of the obtained membrane electrode.

[0160] Table 2 Comparison of performance of hydrogen production by water electrolysis of the embodiment and the comparative example

[0161]

[0162] As can be seen from the results in Table 2, the measured prepared membrane electrode has a significant decrease in ohmic impedance before and after activation. The membrane electrode prepared in Example 1 has the lowest ohmic impedance, which is used to enhance the stability of the membrane electrode. The possible reason is that under the premise of selecting a suitable catalyst, by optimizing the catalyst slurry ratio and suitable spraying parameters, the catalyst is firmly bonded to both sides of the membrane, and the electrochemical performance of the membrane electrode is coordinated to increase, and the impedance is reduced. While ensuring high electrolysis efficiency, the membrane electrode assembly has a longer operating time and higher stability. In the comparative example, the difference in ohmic impedance before and after activation is not large, and the reason lies in the catalyst slurry ratio, spraying parameter setting or catalyst screening.

[0163] As shown in Figure 3, after the membrane electrode was assembled, the constant current density was 10000A / m 2Under the test conditions, the stability operation lasted for 1 month, which shows that the electrode used to prepare the membrane has good performance stability. This has a positive effect on promoting the preparation method of membrane electrodes and their application and development.

[0164] In summary, the present invention prepares a membrane electrode with high thickness uniformity by optimizing the catalyst slurry formula and ultrasonic spraying process. Even if the catalyst types and ratios are different, optimizing the spraying flow rate, spraying speed, spraying interval, spraying time and other parameters can effectively avoid the catalyst slurry from gathering at the edge of the membrane, improve the uniformity of the catalyst slurry on the membrane electrode, and help increase the stability of the performance of the membrane electrode when in use.

[0165] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0166] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a membrane electrode, characterized in that: The following steps are involved: Providing proton exchange membranes; The catalyst slurry is coated on the proton exchange membrane by ultrasonic spraying process, and then dried to obtain the membrane electrode; The spraying direction of the ultrasonic spraying process is from the first end of the proton exchange membrane to the opposite second end, and the spraying starting line end is located at a first distance away from the first end to the second end, and the spraying ending end is located at a second distance away from the second end to the first end, and the first distance and the second distance are both greater than or equal to 5 mm.

2. The method for preparing a membrane electrode according to claim 1, characterized in that: The first distance and / or the second distance is 5 mm to 30 mm.

3. The method for preparing a membrane electrode according to claim 2, characterized in that: The proton exchange membrane is rectangular, and the first end and the second end are two parallel ends of the proton exchange membrane.

4. The method for preparing a membrane electrode according to claim 1, characterized in that: The parameters of the ultrasonic spraying process include: a spraying flow rate of 0.4 ml / min to 10 ml / min, a spraying speed of 10 mm / s to 200 mm / s, and a spraying interval of 5 mm to 20 mm.

5. The method for preparing a membrane electrode according to claim 1, characterized in that: The step of coating the catalyst slurry on the proton exchange membrane by ultrasonic spraying process comprises: The anode catalyst slurry and the cathode catalyst slurry are respectively coated on both sides of the proton exchange membrane by using an ultrasonic spraying process; The anode catalyst slurry comprises an anode catalyst, a first binder and a first solvent in a mass ratio of (5-10): (10-20): (55-100); and / or The cathode catalyst slurry comprises a cathode catalyst, a second binder and a second solvent in a mass ratio of (5-10): (10-20): (55-100).

6. The method for preparing a membrane electrode according to claim 5, characterized in that: The preparation method meets at least one of the following characteristics (1) to (4): (1) The first binder and the second binder are independently selected from one or more of perfluorosulfonic acid resin, polysulfone, and polyphenylene sulfide; (2) the first solvent and the second solvent independently include an alcohol solvent and water in a mass ratio of (25-40): (30-60); (3) The particle size of the anode catalyst is less than or equal to 40 μm; (4) The particle size of the cathode catalyst is less than or equal to 40 μm.

7. The method for preparing a membrane electrode according to claim 6, characterized in that: The preparation method meets at least one of the following characteristics (1) to (4): (1) The binder is a perfluorosulfonic acid resin; (2) The solvent comprises n-propanol and water in a mass ratio of (25-40): (30-60); (3) The anode catalyst is selected from one or more of a Pt / C catalyst, a PtRu / C catalyst, a PtIr / C catalyst, a PtCo / C catalyst, a PtCoMn / C catalyst, a PtNi / C catalyst, a Ru / C catalyst, and an IrRu / C catalyst; (4) The cathode catalyst is a Pt / C catalyst.

8. The method for preparing a membrane electrode according to any one of claims 1 to 7, characterized in that: The temperature of the drying process is 50°C to 90°C.

9. A membrane electrode, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 8.

10. A water electrolysis hydrogen production device, characterized in that: A membrane electrode according to claim 9.